2016
DOI: 10.1097/bsd.0b013e3182a26553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rAAV2-hTGFβ1 Gene Transfer on Matrix Synthesis in an In Vivo Rabbit Disk Degeneration Model

Abstract: Early degenerative NP cells are susceptible to AAV-mediated gene transfer in vitro and in vivo. The rapid and prolonged target protein expressions and increased matrix synthesis indicated that AAV-mediated therapeutic gene transfer can be a promising form of treatment for disk regeneration in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…The AAV vector is well suited for gene transfer in vivo due to its low immunogenicity and high safety. 34 , 35 The observed rapid and prolonged upregulation of protein expression and increased matrix synthesis indicated that AAV-mediated therapeutic gene transfer could be a promising treatment for IDD in vivo . 34 Another study showed that AAV-mediated BMP-7 and SOX9 cotransfection in vitro can promote the synthesis of collagen II in NPCs in a human-degenerative intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AAV vector is well suited for gene transfer in vivo due to its low immunogenicity and high safety. 34 , 35 The observed rapid and prolonged upregulation of protein expression and increased matrix synthesis indicated that AAV-mediated therapeutic gene transfer could be a promising treatment for IDD in vivo . 34 Another study showed that AAV-mediated BMP-7 and SOX9 cotransfection in vitro can promote the synthesis of collagen II in NPCs in a human-degenerative intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 The observed rapid and prolonged upregulation of protein expression and increased matrix synthesis indicated that AAV-mediated therapeutic gene transfer could be a promising treatment for IDD in vivo . 34 Another study showed that AAV-mediated BMP-7 and SOX9 cotransfection in vitro can promote the synthesis of collagen II in NPCs in a human-degenerative intervertebral disc. 36 In this study, a degenerative spine model in rats was generated by acupuncture of the intervertebral disc, and AAV-2 carrying specific genes was injected into rat intervertebral disc tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Different animal models of disc degeneration have been used for regenerative approaches of cell transplantation and gene therapy with applications of bioactive factors and bioscaffolds. 40…”
Section: Introductionmentioning
confidence: 99%
“…In vivo gene therapeutic approaches have been presented in different animal models of disc degeneration by using retrovirus, lentivirus (LV), adenovirus, and adeno-associated virus (AAV) gene delivery vectors. 5358,8389,107,110,136,139,148 Viral vector-based gene therapeutic treatments of DDD can be performed: (I) by direct injection of viral vectors into degenerative IVDs leading to the expression of the therapeutic gene by disc cells transduced within the IVDs; (II) by injection of genetically modified cells into degenerative IVDs that are able to express the therapeutic gene in vivo ; and (III) by transplanting bioscaffolds that are seeded with genetically modified cells enabling the in vivo expression of the therapeutic gene. Biological treatment approaches of DDD are schematically illustrated in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation